Autenticitet og attraktivitet - om vurdering af overensstemmelsen mellem forskellige semiotiske elementer i brugerprofiler på dating-appen Tinder - Hertz, Cecilie Hjelm (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2017)
This article investigates identity work in the reception of user profiles on the social dating app Tinder. The participants expect the profiles’ semiotic elements to interact in a way they find authentic and attractive. They expect consistency between pictures and profile text to evaluate a profile as authentic, and they use the multimodality on Tinder to support their assumptions of the profiles. Furthermore they analyse the profiles based on how these utilise the multimodal possibilities in the app. The participants decipher specific identities based on the profiles’ emblematic features. In the light of these categorizations the participants decide if they find the profile attractive, which results in a swipe left or right.